Religion in China Major Concepts and Minority Positions - Deeg, Max; Scheid, Bernhard (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
Religions of foreign origin have shaped Chinese cultural history much stronger than generally assumed and continue to have impact on Chinese society in varying regional degrees. The essays collected in the present volume put a special emphasis on these "foreign" and less familiar aspects of Chinese religion. Apart from an introductory article on Daoism (the prototypical autochthonous religion of China), the volume reflects China's encounter with religions of the so-called Western Regions, starting from the adoption of Indian Buddhism to early settlements of religious minorities from the Near East (Islam, Christianity, and Judaism) and the early modern debates between Confucians and Christian missionaries. Contemporary religious minorities, their specific social problems, and their regional diversities are discussed in the cases of Abrahamitic traditions in China.